Physical activity level in patients with bronchiectasis: a systematic review of determinants and outcome measures - Emirza, Cigdem; Tiryaki, Pelin; Kaya, Begum Kara; Akyurek, Elcin; Aslan, Goksen Kuran (European Respiratory Soc Journals Ltd, 2021)
[Abstract Not Available]
Keywords: Physical Activity; Bronchiectasis